Assessment of growth and puberty and iron overload in multi-transfused Bangladeshi Thalassemia patients - Hossain, Belayet; Selimuzzaman; Khan, WA; Chowdhury, Nilufar Akter; Rahman, Fazlur; Wahab, A; Sultana, Sajeda; Hasan, Mehedi (Journal of Dhaka National Medical College & Hospital, 2018)
In transfusion dependant Thalassemia patients undergoing transfusion and multiple transfusions along with inadequate chelation therapy leads to iron overload and may cause growth retardation and delayed puberty. The aims of this study are to assay the growth pattern and puberty status and their correlation with iron overload in multi-transfused Bangladeshi Thalassemia patients. This retrospective study assays multi-transfused thalassemic children in Dhaka Shishu (Children) Hospital Thalassemia Centre of Dhaka Shishu (Children) Hospital. Out of total 135 patients, the age range was 12-18 years and mean age of the patients was 14.6±2.5 years and 72(53%) were boys and 63(47%) were girls. The mean weight was 32.25 kg ± 8.45 kg, the mean height was 136.22 cm ± 11.57cm and 81(60.1%) patients were found short with height less than 5th percentile for age. Of the 81 short cases 52 were boys and 29 were girls. Ninety three (69%) cases had delayed puberty, among them boys were 48 (67.6% of boys) and girls were 45 (70.3% of girls). Majority of the girls having primary amenorrhea with few of them having delayed menarche. Of the 93 delayed puberty cases, 61(65.6%) were of short stature and 32(34.4%) were of normal height. The high prevalence of growth retardation and delayed puberty in this study justify the need for vigilant clinical evaluation of multi-transfused thalassemic children for early detection and appropriate treatment of growth retardation and delayed puberty. J. Dhaka National Med. Coll. Hos. 2018; 24 (01): 29-32